165spec1f10

# 165spec1f10 - x 3-4 x + 9) / ( x 3 / 4 + 6) 7 . f ( x ) =...

This preview shows pages 1–2. Sign up to view the full content.

Math 165 Special Assignment I Lowman Fall 2010 Due Thursday, Sept 23 in discussion. The Quiz on Thursday, Sep 23 will be based on this assignment. The general forms (i.e chain rule versions) of the power, log and exponential rules were given in lectures. Part I: 1. List all the rules for ﬁnding limits. 2. List all the rules for ﬁnding derivatives including the general forms of the power rule, log rule and exponential rule. 3. Find the derivative of f ( x ) = 2 x 2 + x by using the limit deﬁnition of the derivative. 4. Find the following limits: (a) lim x 3 2 x +3 x - 3 (b) lim x 3 9 - x 2 x - 3 (c) lim x 3 x - 3 x - 9 (d) lim x →∞ 1 x (e) lim x →-∞ 1 x (f) lim x 0 + 1 x (g) lim x 0 - 1 x (h) lim x 2 (3 x 2 + 2) / ( q (4 x 3 ) + 2 x ) 1

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Part II: Find df dx for the following functions and simplify answers: 1 . f ( x ) = 1 3 x 6 - 2 x 2 + 25 x 2 . f ( x ) = 5 x 4 3 . f ( x ) = 25 x 2 + x 4 . f ( x ) = 1 / ( x 10 ) 5 . f ( x ) = x 2 + 1 / ( x ) 6 . f ( x ) = (6
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: x 3-4 x + 9) / ( x 3 / 4 + 6) 7 . f ( x ) = (7 x ) / (1 + x 2 ) 8 . f ( x ) = (1-x 3 ) 4 9 . f ( x ) = (1-5 x 3 ) 1 / 3 10 . f ( x ) = (( x 3-2 x + 1) 2 ) 1 / 3 11 . f ( x ) = q ( x 2-2 x + 1) / (1-x 3 ) 12 . f ( x ) = ((3 x 2 + 5 x ) / (1-5 x 3 )) 4 13 . f ( x ) = a 3 x 3 + a 2 x 2 + a 1 x + a 14 . f ( x ) = ln x 15 . f ( x ) = x ln x 16 . f ( x ) = ln 3 x 2 x 4 17 . f ( x ) = ( t + ln t ) 3 / 2 18 . f ( x ) = ln(2 x 2 + 1) 19 . f ( x ) = e x 20 . f ( x ) = e x 2 +1 21 . f ( x ) = e-3 x x 2 +1 22 . f ( x ) = xe 2 x 23. Use implicit dierentiation to nd dy dx when 20 + 2 x = 4 x 2 + x 3 y 4 24. Use the chain rule to nd dy dx if y = ( x 2 +2) 3-3( x 2 +2) 2 +1 2...
View Full Document

## 165spec1f10 - x 3-4 x + 9) / ( x 3 / 4 + 6) 7 . f ( x ) =...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online